Pengaruh Atribut Produk Hijau, Green Perceived Value, dan Kesadaran Lingkungan Terhadap Keputusan Pembelian Hijau pada Produk Avoskin di Yogyakarta - Mamonto, Bayu Bachtiar; Nuvriasari, Audita (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the effect of green product attributes, green perceived value, and environmental awareness on green purchasing decisions on Avoskin products in Yogyakarta. The sample in this study were 100 respondents using non-probability sampling method. The instrument test results state that the data in the study are valid and reliable. The results of the classical assumption test state that the data in this study are normally distributed and produce a regression model that is free from multicollinearity and heteroscedasticity. The results of this study prove that: (1) Green Product Attributes have a negative and significant effect on green purchasing decisions on Avoskin products in Yogyakarta. (2) Green Perceived Value has a negative and significant effect on green purchasing decisions on Avoskin products in Yogyakarta. (3) Environmental Awareness has a positive and significant effect on green purchasing decisions on Avoskin products in Yogyakarta